Strategi Pencegahan Inses dalam Perspektif Hukum Islam dan Ilmu Kesehatan Masyarakat - Muhammad Achwan; Dyah Erlina Sulistyaningrum; Suryadi Suryadi; Ucik Ernawari; Jibril Olaniyi Ayuba; Maria Endah Yosepin Listyowati (STIKes Ibnu Sina Ajibarang, 2025)
Incest is a form of sexual violence that not only violates social and religious norms but also causes serious physical and mental health impacts on victims. In the context of Islamic law, incest is considered a heinous act that violates sharia and may be subject to hudud or ta'zir punishment. Meanwhile, in public health, incest is viewed as an issue that poses long-term risks, such as genetic disorders, psychological trauma, and socio-economic consequences. This study aims to examine prevention strategies for incest through a holistic approach combining Islamic legal principles and public health perspectives. The method used is qualitative research with a normative literature review and descriptive-analytical approach. The findings indicate that incest prevention can be achieved through strengthening religious values within families, sharia-based sexual education, and improving mental health services and case reporting systems in the community. The implications of this study highlight the importance of synergy between religious institutions, healthcare professionals, and public policy in establishing effective and sustainable incest prevention systems.